#TITLE_ALTERNATIVE# - FAJRI YAYUSMAN (NIM 15107074); Pembimbing: Prof. Ketut Wikantika, Ph.D., dan Daniel Adi Nugroh, LISSA
In the forest and plantation potential identification and management, the need of structural data is very important. Oil palm plantations, which have high potential in environmental and the economy sector, requires good management and planning. Measurement of structural parameters on oil palm plantations will provide the necessary information in order to monitoring and management of the area. Measurement process on large areas can be supported by remote sensing technology with high accuracy, namely Light Detection and Ranging or LIDAR. LIDAR technology with the advantages of multiple returns is not only able to scan the forest structure from the top side only, but also can measure parts of the canopy of trees and other objects underneath. Therefore, modeling of oil palm plantations can include the whole structure of the vegetation with more accuracy. The returns of laser pulse is also obtained from the soil surface makes it possible to perform modeling of land surface elevation under tree canopy in the form of Digital Terrain Model (DTM). By converting the point cloud into raster, the elevation of tree canopy can be modeled into Canopy Height Model (CHM) by subtracting the Digital Surface Model (DSM) and the DTM. Based on this research, tree height distributions in the area are 49.15% between 10.3-20.3 meter, 42.75% between 0.3-10.3 meter, 8.1% between 0-0.3 meter, and 0.02 % between 20.3-30.3 meter, while the total volume of canopy is 8684.242 m3.